2007
DOI: 10.1016/j.jsat.2006.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Counselor perceptions of organizational factors and innovations training experiences

Abstract: Because work environment is central to understanding job performance, drug counselor perceptions of their programs and their skills were examined in relation to their attitudes about innovations training and its utilization. Latent profile analysis of measures on organizational climate and staff attributes for 1047 counselors from 345 programs defined three categories of counselors -labeled as Isolated, Integrated, and Exceptional. All had generally positive views of their professional skills, although the Iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 50 publications
3
45
2
Order By: Relevance
“…The finding is consistent with some research finding greater support for evidence-supported treatment approaches in more stressful organizational environments (Fuller et al, 2007) and with studies finding greater support for 12-step treatment approaches in supportive organizational environments (Moos & Moos, 1998). Still, most studies addressing organizational climates and the implementation of EBPs have concluded that organizations with stressful climates in which staff are overloaded or emotionally exhausted are not well suited for implementation of new, innovative EBPs (Joe, Broome, Simpson, & Rowan-Szal, 2007;Simpson & Flynn, 2007). How unfortunate and paradoxical then if frontline staff members' efforts to use new EBPs might prompt the development of unfavorable organizational climates.…”
Section: Discussionsupporting
confidence: 84%
“…The finding is consistent with some research finding greater support for evidence-supported treatment approaches in more stressful organizational environments (Fuller et al, 2007) and with studies finding greater support for 12-step treatment approaches in supportive organizational environments (Moos & Moos, 1998). Still, most studies addressing organizational climates and the implementation of EBPs have concluded that organizations with stressful climates in which staff are overloaded or emotionally exhausted are not well suited for implementation of new, innovative EBPs (Joe, Broome, Simpson, & Rowan-Szal, 2007;Simpson & Flynn, 2007). How unfortunate and paradoxical then if frontline staff members' efforts to use new EBPs might prompt the development of unfavorable organizational climates.…”
Section: Discussionsupporting
confidence: 84%
“…Second, we studied one type of health care organization, so future research should examine other health care settings and other industries. While our response rate was similar or higher than some other studies of counselors (Duraisingam, Pidd, & Roche, 2009;Forman, Bovasso, & Woody, 2001;Gallon, Gabriel, & Knudsen, 2003;Joe, Broome, Simpson, & Rowan-Szal, 2007), it was lower than the 70% response rate achieved in a large study of counselors working in the National Drug Abuse Treatment Clinical Trials Network (McCarty et al, 2007). We cannot address the extent to which non response at the level of individual counselors may bias our results, which is a limitation of this research.…”
Section: Discussioncontrasting
confidence: 70%
“…The PTN, therefore, can serve as a strategic planning tool and is related to core elements of a more comprehensive appraisal of organizational functioning that can be obtained using the Organizational Readiness for Change (ORC; Lehman et al, 2002) assessment. The ORC is related to client performance in treatment (Broome, Flynn, Knight, & Simpson, 2007;Greener, Joe, Simpson, Rowan-Szal, & Lehman, 2007) and has utility for predicting program readiness to adopt innovations (Fuller et al, 2007;Joe, Broome, Simpson, & Rowan-Szal, 2007;Saldana, Chapman, Henggeler, & Rowland, 2007). Not surprisingly, more favorable counselor ratings of workshop training predict subsequent implementation of the training materials (Bartholomew, Joe, Rowan-Szal, & Simpson, 2007).…”
Section: Introductionmentioning
confidence: 99%